Natural products of Silk Road plants - Cooper, Raymond; Deakin, Jeffrey John (Boca Raton, FL : CRC Press, 2021)
"This volume, part of a world-wide series, has been prepared for university students of chemistry and ethno-botany and for those wishing to broaden knowledge. Plants, many indigenous to countries along the trading routes of the Silk Road, yielded medicines, cereals, spices, beverages, dyes and euphoric and exotic compounds. The book opens a window on a vast region of Asia not well described for its flora providing new and fresh insights upon: significant plants, some endangered traditional and modern applications of extracts the biochemical and pharmacological properties of extracts The Silk Road, a complex network of trade routes linking China with the rest of the Eurasian continent by land and sea, fostered transformation of the ethnic, cultural and religious identities of diverse peoples. The significance of the Silk Road is being revived today through immense investment by China and other eastern countries in major schemes of transport infrastructure"--
OCLC-licensed vendor bibliographic record.
Keywords: Phytochemicals -- History; Botanical chemistry -- History; Ethnobotany -- History; Medicinal plants -- History; Natural products -- History; Plants -- Social aspects -- History -- To 1500.; Silk Road -- History; HEALTH & FITNESS / Herbal Medications; SCIENCE / Life Sciences / Botany; SCIENCE / Chemistry / General